North American tunneling `96 : proceedings of the International Conference on North American Tunneling ' 96 and the 22nd. general assembly of the International Tunneling Association , Washington, DC, USA, 21-24 April 1996 - International Conference on North American Tunneling (22nd : 1996 : Washington, DC, USA); Ozdemir, Levent (Rotterdam : A.A. Balkema, 1996)
03